2018
DOI: 10.4187/respcare.05876
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary Percussive Ventilation as an Airway Clearance Technique in Subjects With Chronic Obstructive Airway Diseases

Abstract: The systematic use of IPV as an airway clearance technique in chronic obstructive airway diseases is not supported by sufficiently strong evidence to recommend routine use in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
(148 reference statements)
2
21
0
3
Order By: Relevance
“…They found a reduction in the duration of hospitalisation and have observed an improvement in gas exchange only during the exacerbation phase in patients with chronic obstructive airway disease. In patients with cystic fibrosis, no difference was observed in the static and dynamic lung volume 26 . Cough is usually not impaired in patients with chronic obstructive airway disease and cystic fibrosis, thus potentially explaining the contrasting results.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…They found a reduction in the duration of hospitalisation and have observed an improvement in gas exchange only during the exacerbation phase in patients with chronic obstructive airway disease. In patients with cystic fibrosis, no difference was observed in the static and dynamic lung volume 26 . Cough is usually not impaired in patients with chronic obstructive airway disease and cystic fibrosis, thus potentially explaining the contrasting results.…”
Section: Discussionmentioning
confidence: 83%
“…The results of studies using IPV and HFCWC for other pathologies show similarities and differences as compared with our results. Reychler et al (2018) have performed a systematic review and compared IPV with other airway clearance techniques. They found a reduction in the duration of hospitalisation and have observed an improvement in gas exchange only during the exacerbation phase in patients with chronic obstructive airway disease.…”
Section: Discussionmentioning
confidence: 99%
“…IPV is a respiratory physiotherapy technique that consists in delivery of small volumes of air into the airways, typically in the 1-10 Hz frequency and 10-50 cmH 2 O pressure ranges (Reychler et al, 2018). It is currently used to mobilize secretions, promote lung recruitment and improve gas exchange in chronic conditions such as neuromuscular diseases, cystic fibrosis, and chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that the use of HFCWO in CF may lead to a decline in lung function, oxygen desaturation and exacerbations (50)(51)(52). Current evidence also does not suggest a benefit of IPV in patients with CF (53).…”
Section: B Cystic Fibrosismentioning
confidence: 99%